Examining the Gender Differentials in the Application for STEM Fields: Findings from the University of Lagos - Franca Attoh; Yemisi Obashoro-John; Maryam Quadri; Femi Olowu; Abimbola Durojaiye (Unilag Journal of Humanities, 2019)
Building on secondary data, this paper seeks to make two contributions to literature.First, to present a description of the sex differentials in course applications into Nigerianuniversities, using the University of Lagos as a sample and second, to describe thevariation in the selection of courses in the fields of Science, Technology, Engineeringand Mathematics (STEM) by prospective students that are females. Findings showed thatfemale applications for degree programmes were higher than male applications in mostfields, including some core science fields which involve human-oriented professions likepharmacology and medicine. Nevertheless, the overall statistics revealed that theproportion of male applicants were fractionally higher during the four sessions underreview. The sex differentials were highest in engineering and environmental sciencesfields where male applications outnumbered female applications by a ratio of about threeto one. Furthermore, female applicants were more likely to choose biological, peopleoriented and care-centred fields, leading to female apathy towards engineering and othertechnical programmes, especially those with mathematics, physics and geography as coresubjects. We, therefore, recommend the development of nationwide programmes aimed atdispelling gendered misconceptions about certain fields, especially STEM fields. This isvery essential in a world where science and technology define national economies.Nigeria cannot afford to leave half her population behind.